ANALISIS PERKEMBANGAN LUAS AREAL DAN PRODUKSI TANAMAN HIAS MAWAR DI PROVINSI KALIMANTAN TIMUR - Khairan, Adinda Rizky; Ardi, Muhammad; Jannah, Gyna Raudatul; Rahmadhani, Deva Allegra; Cahyono, Yoga Agusta Dwi; Mariyah, Mariyah (Universitas Negeri Gorontalo, 2025)
The national demand for roses experienced an increase from 2021 to 2023. However, in East Kalimantan Province, rose demand declined during the same period. This research examines the development of rose production in East Kalimantan. The objectives are to: 1) identify the trends in rose production area expansion and 2) analyze the development of rose production quantities in the province. The research employs library research and descriptive quantitative methods. Data were sourced from the National Bureau of Statistics (BPS) and the East Kalimantan Provincial Bureau of Statistics, along with relevant references regarding ornamental plant production in Indonesia and East Kalimantan. From 2021 to 2023, there was a significant decline in both the rose production area and output in East Kalimantan. This reduction in cultivation area was primarily due to land-use conversion triggered by population growth. Meanwhile, unpredictable weather and rural economic challenges contributed to the decrease in rose production. To address this issue, priority should be given to policies promoting the protection of productive land, technological innovation, and business diversification for farmers to boost rose cultivation area and output in East Kalimantan.